Integrasi WhatsApp Gateway dan Cloud Computing pada Sistem Absensi Digital Terpadu Siswa (SAGITA) - Gustiawan Maula Rizki; Fathoni Dwiatmoko; Agus Komarudin (Universitas Darul Ulum, 2026)
The integration of Information and Communication Technology (ICT) in vocational high schools demands agile and accurate administrative governance. Manual attendance monitoring often collides with data accuracy issues and recapitulation inefficiency. This study aimed to design, develop, and evaluate the Integrated Student Digital Attendance System (SAGITA) utilizing a cloud computing architecture at SMK NU Kaplongan, accommodating 1,186 students across 38 study groups. The system integrated the Google Workspace ecosystem (Google Forms and Sheets) with Google Apps Script (GAS) and a local WhatsApp Gateway API for real-time information broadcasting. Employing an applied research methodology with a prototyping approach, the evaluation was conducted through functional testing (Black-box) and administrative impact testing (Pre-test/Post-test). The results showed that the system successfully sent notifications with an average latency of 3-5 seconds. The administrative evaluation indicated a measurable efficiency in recapitulation time and a decrease in reporting delays. The system's continuity relies heavily on physical supporting infrastructure, including the availability of a Virtual Private Server (VPS), a Public IP, and an Uninterruptible Power Supply (UPS). This low-code model offers a cost-effective alternative administrative solution for large-scale educational institutions